Variasi Bentuk dan Warna Sisik Sayap Kupu-Kupu dan Ngengat: Variations in Shape and Color of Butterfly Wing Scales and Moths - Marchika Rimadhanti Irmanda Rani; Tri Atmowidi; Tri Heru Widarto (Jurnal Sumberdaya Hayati, 2023)
Butterflies and moths are members of Lepidoptera with the main characteristic of having two pairs of membranous wings covered with scales. The wings of butterflies and moths have colored patterns that can be used as protection from predators. The aim of this study was to compare the shape, size, and color variations of the scales on the wings of butterflies and moths. Samples of butterflies and moths were collected from the Dramaga Bogor Agricultural University campus. In this study, 11 species of butterflies were used belonging to three families, namely Pieridae, Nymphalidae, and Papilionidae, and 9 species of moths in four families, namely Erebidae, Geometridae, Hesperiidae, and Uraniidae. Observation of scales was carried out with a compound microscope connected to a camera, and measured using imageJ. The shape of the wing scales of butterflies and moths was elongated and widened with the base of the scales and the number of teeth on the distal part varied. The shape of the serrations on the butterfly scales tends to be rounded, while on the moth it is tapered. Larger scale sizes are found on light-colored butterfly scales and dark-colored moth scales.